2013
DOI: 10.1161/atvbaha.113.301901
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cardiovascular Involvement in Pseudoxanthoma Elasticum Families

Abstract: Objective-Pseudoxanthoma elasticum (PXE) is an autosomal recessive connective tissue disorder with involvement of the skin, the retina, and the cardiovascular system. Cardiovascular involvement is mainly characterized by mineralization and fragmentation of elastic fibers of blood vessels and premature atherosclerosis. We conducted an ultrasound study to investigate the cardiovascular phenotype and to propose recommendations for the management of patients with PXE and heterozygous ABCC6 mutation carriers. Appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 42 publications
1
49
1
7
Order By: Relevance
“…Some publications describe cardiovascular manifestations of PXE. This inherited multisystem disorder seems to increase the cardiovascular risk and is associated with an increased occurrence of atherosclerotic changes [7][8][9]. However, untill today there is little knowledge about the distribution and the pathomechanism of atherosclerosis in patients with PXE.…”
Section: Discussionmentioning
confidence: 99%
“…Some publications describe cardiovascular manifestations of PXE. This inherited multisystem disorder seems to increase the cardiovascular risk and is associated with an increased occurrence of atherosclerotic changes [7][8][9]. However, untill today there is little knowledge about the distribution and the pathomechanism of atherosclerosis in patients with PXE.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, increased risk of cardiovascular complications has been observed not only in patients with PXE but also in heterozygous ABCC6 mutation carriers. In particular, heterozygous carriers of the loss-of-function mutation p.R1141X, the most common mutation in the Caucasion populations, is associated with a strong increase in the prevalence of coronary artery disease [1719]…”
Section: Clinical Featuresmentioning
confidence: 99%
“…To our knowledge, the latest study regarding the vascular stiffness of PXE patients, was performed by Campens et al in 2013 and showed that PXE had a higher PWV compared to controls. They concluded, that PXE patients' aorta was stiffer (1).…”
Section: Discussionmentioning
confidence: 98%
“…Characteristic clinical symptoms of PXE include typical skin signs including yellowish papules and inelastic skinfolds especially on the lateral neck, the axillae and the popliteal fossae (1,2). Other characteristic signs are ophthalmologic alterations like angoid streaks or retinal pigment epithelium atrophy and cardiovascular manifestations such as a high prevalence of peripheral artery disease (PAD), intermittent claudication or chronic vascular occlusions which are mostly localized in the lower limb specially the femoral arteries (13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation